Technical efficiency associated with production inputs according to crop age among oil palm smallholders in Johor, Malaysia - Tijani, Bulama Abiso (2017)
The study measured technical efficiency associated with production inputs according to crop age among oil palm smallholders in Johor, Malaysia. Primary data were collected through multi-stage sampling procedure from a sample size of 450 independent oil palm smallholders randomly selected non-proportionately under young, prime and old crop age categories in ten (10) production units of Johor, Malaysia. Descriptive Statistics, DEA, DEA-bootstrap, FDH, Order-m, Order-alpha, SFA and PFF using COLS were employed to estimate and compare technical, allocative and economic efficiencies. Analysis of variance (one way ANOVA) was used to test for significance difference in mean TE, AE and EE efficiency according to crop age among smallholders while Tobit and OLS models were used to analyze the determinants of inefficiency. The mean technical efficiency (TE) estimates based on the variable returns to scale (VRS) for smallholders under young, prime and old crop age categories were 0.9601, 0.9412 and 0.9757 respectively while based on constant returns to scale (CRS) were 0.8616, 0.7092 and 0.9055 respectively. The mean SE estimates were 0.8986, 0.7466 and 0.9282 for the smallholders under young, prime and old crop age categories respectively. The mean allocative efficiency (AE) for the smallholders under young, prime and old crop age categories were 0.6248, 0.5905 and 0.6260 respectively while mean economic efficiency (EE) were 0.6146, 0.5286 and 0.5981 respectively. The finding also shows that there was significant difference in the mean TE and EE of the smallholders under young, prime and old crop age categories at 1% but no significant difference exists in the mean AE among the smallholders. The study also shows that age of farmer, education, household size, experience, off-farm income, oil palm income, government intervention, access to credit, age of crop squared, fertilizer, land clearing, extension contact, membership of smallholders association, replication of pesticides application and pest & weed control method have negative relationship with technical, allocative and economic inefficiency. The study identified unavailability of labour, low price for produce, high cost of farm inputs, low yield and high cost of labour as the major oil palm production problems in the study area. There is need to re-strategies the extension program for effective monitoring and supervision of the smallholders’ in order to ensure that they comply with recommended inputs use in order to enhance their efficiency levels. The study also recommend policies that would improve the quality of adult education extension program to educate the oil palm smallholders who owned young and prime crop age categories on how to use the various combinations of farm resources that can minimize cost of production appropriately. The oil palm smallholders should improve on their cooperative activities to enjoy economies of scale since they experience high cost of production which affects their profit.